Cultural Diversity and Bioethics - K Aramesh (Tehran University of Medical Sciences, 2008)
My main question in this article is as follows: "to which extent cultural diversity should be permitted to influence bio-ethical judgments?" There are cultural heritages, values and traditions which are acceptable and respectable and there are ones which are not so. In this article I concluded that our reasoning based on common ethical sense can guide us through such differentiations. Human dignity as a common notion among most alive cultures and religions thorough the world, can be relied for sketching a plan for further dialogues in this regard.